Políticas de formação continuada de professores da rede estadual de ensino do estado do Paraná (1996-2017): entre a certificação e os desafios político-pedagógicos - Tortato, Marcia Adriane Falat (2018)
The present dissertation aims to study the public policies of Continuing Education of Basic Education Teachers, in the period after LDB / 96 until 2017. It is a fact that the country has not lacked public policies for continuing education, many were and are formulated and implemented in the three spheres of the Brazilian state - federal, state and municipal. However, there remain doubts about what these policies are proposing and what their emancipatory potential. As a result, we question the meanings of the policies of continuing education of the Basic Education teachers of the State of Paraná in the period immediately after the LDB / 96 to 2017. The general objective is to make explicit the meanings of the policies of continuing education of teachers of the State of Paraná. Basic Education in the State of Paraná, in the post LDB / 96 period. It can be understood as the ways of being of politics, which can present themselves in different ways in the reality of teacher education. And the following specific objectives: 1 - To explain the policies of continuous formation expressed in the legislation with emphasis in those of the State of Paraná; 2- To unveil the meanings of the public policies of continuous formation that the teachers of the State Network of Education of Paraná point. It is a research oriented by the dialectical historical materialist perspective of social phenomena. Dialectics makes it possible to apprehend reality, the result of human activity in its materiality and movement (history). In this approach, we aim to analyze the real in the historical context, providing the understanding of the totality and its transformation. The scope of the proposed objectives was based on the literature review of the object in question, a study of the national legislation pertinent to the continuing education of teachers, in the historical context of the late 1980s, when the 1988 Citizen Constitution of LDB 9394/96 and subsequent legislation to this day. Also, research was carried out on the educational policies of the State of Paraná and legislations that regulate the continuing education of the teachers of the Paraná educational network. In addition, through a questionnaire, teachers were asked about the policies of continuing education. The results make it possible to point out that there has been a lack of policies for the continuous training of teachers, some of which are carried out with great difficulties, and that in the state of Paraná the PDE / PR stands out as an important policy due to its nature, which teachers attribute to continuing education, emphasizing the way of being of the certification, it is defended the necessity of the political pedagogical sense of the policies of the continuous formation of teachers.